2019
DOI: 10.3390/en12214088
|View full text |Cite
|
Sign up to set email alerts
|

Geology and Petroleum Systems of the East China Sea Basin

Abstract: The back-arc East China Sea Basin lies on extended continental crust at the leading edge of the Eurasian plate. In this study, the basins are described and subdivided according to their tectono-stratigraphic evolution. In order to distinguish between different phases of deformation in basin development, standard basin evolution patterns related to geodynamic drivers are identified as a first step. On the basis of this, standard patterns are recognized in the sedimentary sequences that characterize the area and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Alternatively, it is also possible that Oligocene sediment in the Xihu Sag and EDB were sourced from nearby structural highs, highs to the north, and/or from the Taiwan‐Sinzi belt to the east (Qin et al, ; Wang et al, ; Yang et al, ). Several recent provenance studies have concluded that the Precambrian zircons in Oligocene units in the Xihu Sag were sourced from basement to the north of the Xihu Sag (Wan & Zhang, ; Qin et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, it is also possible that Oligocene sediment in the Xihu Sag and EDB were sourced from nearby structural highs, highs to the north, and/or from the Taiwan‐Sinzi belt to the east (Qin et al, ; Wang et al, ; Yang et al, ). Several recent provenance studies have concluded that the Precambrian zircons in Oligocene units in the Xihu Sag were sourced from basement to the north of the Xihu Sag (Wan & Zhang, ; Qin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent provenance studies have concluded that the Precambrian zircons in Oligocene units in the Xihu Sag were sourced from basement to the north of the Xihu Sag (Wan & Zhang, ; Qin et al, ). Although this possibility cannot be evaluated directly because the age of potential basement sources is unknown, Proterozoic rocks that are an eastward extension of the South China Block may underlie the region (Wang et al, ; Yang et al, ). Early international boreholes located close to the Hupingjiao Uplift, north of Xihu Sag, encountered a series of gneiss and schist (JDZ‐V‐2 by Japan, KV‐1 by South Korea) interpreted to be Precambrian in age (Wang et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Division of strata and tectonic stages of the ECSSB (AfterYang, Cui, & Zhang, 2010) its strike-slip property, and there are also some small half-grabens developed inside it. By comparison, in the east, structural types of the Minjiang and the Jilong sags are consistent.Without any flower-like structures, the two sags are characterized by extensional structures like grabens and half-grabens.…”
mentioning
confidence: 99%